Increasing Quality and Frequency of Goals-of-Care Documentation in the Highest-Risk Surgical Candidates: One-Year Results of the Surgical Pause Program. Issue 2 (24th April 2023) - Oyekan, Anthony A.; Lee, Joon Y.; Hodges, Jacob C.; Chen, Stephen R.; Wilson, Alan E.; Fourman, Mitchell S.; Clayton, Elizabeth O.; Njoku-Austin, Confidence; Crasto, Jared A.; Wisniewski, Mary Kay; Bilderback, Andrew; Gunn, Scott R.; et al.
Abstract : Background: Patient values may be obscured when decisions are made under the circumstances of constrained time and limited counseling. The objective of this study was to determine if a multidisciplinary review aimed at ensuring goal-concordant treatment and perioperative risk assessment in high-risk orthopaedic trauma patients would increase the quality and frequency of goals-of-care documentation without increasing the rate of adverse events. Methods: We prospectively analyzed a longitudinal cohort of adult patients treated for traumatic orthopaedic injuries that were neither life- nor limb-threatening between January 1, 2020, and July 1, 2021. A rapid multidisciplinary review termed a "surgical pause" (SP) was available to those who were ≥80 years old, were nonambulatory or had minimal ambulation at baseline, and/or resided in a skilled nursing facility, as well as upon clinician request. Metrics analyzed include the proportion and quality of goals-of-care documentation, rate of return to the hospital, complications, length of stay, and mortality. Statistical analysis utilized the Kruskal-Wallis rank and Wilcoxon rank-sum tests for continuous variables and the likelihood-ratio chi-square test for categorical variables. Results: A total of 133 patients were either eligible for the SP or referred by a clinician. Compared with SP-eligible patients who did not undergo an SP, patients who underwent an SP more frequently had goals-of-care notes identified (92.4% versus 75.0%, p = 0.014) and recorded in the appropriate location (71.2% versus 27.5%, p < 0.001), and the notes were more often of high quality (77.3% versus 45.0%, p < 0.001). Mortality rates were nominally higher among SP patients, but these differences were not significant (10.6% versus 5.0%, 5.1% versus 0.0%, and 14.3% versus 7.9% for in-hospital, 30-day, and 90-day mortality, respectively; p > 0.08 for all). Conclusions: The pilot program indicated that an SP is a feasible and effective means of increasing the quality and frequency of goals-of-care documentation in high-risk operative candidates whose traumatic orthopaedic injuries are neither life- nor limb-threatening. This multidisciplinary program aims for goal-concordant treatment plans that minimize modifiable perioperative risks. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.